Reakcja Unii Europejskiej na wybory prezydenta Ukrainy w 2010 r. - Lugina, Olena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
The paper presents the attitude of the EU to the Presidential elections in Ukraine which took place this year. It discusses the statements of leading EU politicians related to Brussels–Kiev relations at the time, the impact of the elections on the further development of cooperation between the EU and Ukraine, as well as the activities of the European Parliament intended to support the pro-European policy of Ukraine, headed by the recently elected President Viktor Yanukovich. The paper also presents articles that reported the campaign and its results published in the main European newspapers, such as „Süddeutsche Zeitung”, „Spiegel”, „The Economist”, „The Financial Times”, „Liberation”,„Corriere della Sera” and others, which exerted a significant influence on shaping EU public opinion on presidential elections in Ukraine. The author pays particular attention to the analysis of the first visit of the new Ukrainian President, Viktor Yanukowich, to Brussels. It resulted in the key priorities of the EU-Ukrainian cooperation under the new political circumstances being established.